Thermal limits of two biting midges, Culicoides imicola Kieffer and C. bolitinos Meiswinkel (Diptera: Ceratopogonidae) - Verhoef, F Arné (BioMed Central, 2014)
BACKGROUND: Culicoides imicola Kieffer and Culicoides bolitinos Meiswinkel (Diptera: Ceratopogonidae) are both of veterinary importance, being vectors of Schmallenberg, bluetongue and African horse sickness (AHS) viruses. Within South Africa, these Culicoides species show a marked difference in their abundances according to altitude, with C. imicola highly abundant in lower altitudes, but being replaced as the dominant species by C. bolitinos in cooler, high-altitude regions. METHODS: The thermal physiology of field collected adults of each species was determined to evaluate whether it could account for differences in their distribution and abundance. Critical thermal maxima (CT(max)) and minima (CT(min)), as well as upper and lower lethal temperatures (ULT and LLT) were assessed after acclimation temperatures of 19ˌC, 24ˌC and 29ˌC. Critical thermal limits were determined using an ecologically relevant rate of temperature change of 0.06ˌC.min(−1). RESULTS: Significant differences in CT(min) and CT(max) were found between acclimation temperatures for C. imicola and C. bolitinos. In C. bolitinos, the LLT of individuals acclimated at 24ˌC was significantly improved (LLT(50) = −6.01ˌC) compared with those acclimated at the other temperatures (LLT(50) = −4ˌC). Acclimation had a weak (difference in LLT(50) of only 1ˌC) but significant effect on the LLT of C. imicola. When CT(min), CT(max), LLT and ULT were superimposed on daily maximum and minimum temperature records from locations where each tested Culicoides species is dominant, it was found that temperatures frequently declined below the CT(min) and LLT of C. imicola at the location where C. bolitinos was dominant. CONCLUSIONS: The distribution and abundance of C. imicola is likely directly constrained by their relatively poor tolerance of lower temperatures. Results for C. bolitinos suggest that the adult phase is hardy, and it is hypothesised that the thermal biology of other life stages could determine their range. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/1756-3305-7-384) contains supplementary material, which is available to authorized users.